The Tradition of Salat Hadiyah and Tahlilan in Gunungmanik Village: A Legacy of Prayers for Ancestors - Sahid, Toto Ahmad (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2025)
Abstract: Purpose- This study explores the tradition of Salat Hadiyah and Tahlilan in Gunungmanik Village, aiming to examine its religious significance and social function within the local Muslim community. Design/methods/approach- The research adopts a qualitative descriptive approach, utilizing field observations, interviews with religious and community leaders, and a review of theological sources to understand both practice and perception. Findings- The findings reveal that these rituals serve not only as spiritual offerings for the deceased but also as a means of strengthening communal ties and preserving intergenerational religious values. Despite ongoing theological debates regarding the transfer of worship rewards to the deceased, the community largely upholds the practice, supported by interpretations from salaf and khalaf scholars. Religious and local leaders play a key role in sustaining and promoting this tradition. Research Implications- This study emphasizes the need to strengthen public understanding of Islamic teachings in harmony with local culture. Preserving practices like Salat Hadiyah and Tahlilan as part of religious and cultural heritage is vital to ensuring their relevance and acceptance in contemporary Muslim society.